Characterization of minerals, metals, and materials 2016 : proceedings of a symposium sponsored by the Materials Characterization Committee of the Extraction and Processing Division of the Minerals, Metals & Materials Society (TMS) held during TMS 2016, 145th Annual Meeting & Exhibition, February 14-18, Downtown Nashville, Tennessee, Music City Center - Ikhmayies, Shadia J.; Li, Bowen (Materials scientist); Carpenter, John S.; Hwang, Jiann-Yang; Monteiro, Sergio Neves; Li, Jian (Materials scientist); Firrao, D.; Zhang, Mingming (Metallurgist); Peng, Zhiwei; Escobedo, Juan Pablo, 1978-; Bai, Chen-Guang (Springer, 2016)
Characterization is an important and fundamental step in material research before and after processing. This book focuses on the characterization of minerals, metals, and materials as well as the application of characterization results on the processing of these materials. It is a highly authoritative collection of articles written by experts from around the world. The articles center on materials characterization, extraction, processing, corrosion, welding, solidification, and method development. In addition, articles focus on clays, ceramics, composites, ferrous metals, non-ferrous metals, minerals, electronic, magnetic, environmental, advanced and soft materials. This book will serve the dual purpose of furnishing a broad introduction of the field to novices while simultaneously serving to keep subject matter experts up-to-date.